SUSTAINABLE DEVELOPMENT WORKING GROUP. 2011-13 WORK PLAN. MARCH 2011. - Sustainable Development Working Group (SDWG) (Sustainable Development Working Group (SDWG), 2011)
Arctic Council working group Sustainable Development Working Group (SDWG)'s work plan for 2011-2013, submitted to the Arctic Council's 7th Ministerial Meeting in Nuuk, Greenland, May 12 2011.